Design a Chicken Coop Monitoring System Based on the Internet of Things - Mamay Syani; Despawana; Eryan Ahmad Firdaus; Dadan Mulyana (NUANSA INFORMATIKA, 2024)
Internal and external factors greatly influence the optimal breeding of chickens in the maintenance of chickens, with temperature and humidity being one of the external factors that greatly influences. Improper ambient temperature can cause losses to the chicken farmer as well as a decrease in productivity, while in practice it is necessary to monitor or check the control consistently to monitor the temperature of the coop. Temperature and humidity monitoring  manually are less efficient, so the tools in this study aim to help farmers to facilitate monitoring that can be done through devices with accurate results. This tool is assisted by a DHT11 sensor, lamps, fans, and LCD in temperature monitoring. supported by the application of IoT, which makes it easier to monitor via devices. Test results on components and software show that all devices and software can function as they should. The data from the experimental test results of 15 tests conducted in the laboratory indicate that the tool can detect an average relay delay time of 1 of 0.836 seconds, the lamp in response to the temperature drop of 1.271 seconds, the delay from relay 2 by 0.466 seconds, and the fan in response to the temperature increase of 0.596 seconds.